Optics inspections and tests : a guide for optics inspectors and designers - Hausner, Michael (Bellingham, Washington : SPIE Press, 2017)
'This book instructs inspectors and designers of optical elements and assemblies with the primary means of inspection and testing, as well as the relevant tools and instruments'--
Includes bibliographical references and index.
Keywords: Optical materials -- Quality control; Optical materials -- Testing